Space, Time and Molyneux's Question. - Richardson, Louise (Ratio, 2014)
Whatever the answer to Molyneux's question is, it is certainly not obvious that the answer is 'yes'. In contrast, it seems clear that we should answer affirmatively a temporal variation on Molyneux's question, introduced by Gareth Evans. I offer a phenomenological explanation of this asymmetry in our responses to the two questions. This explanation appeals to the modality-specific spatial structure of perceptual experience and its amodal temporal structure. On this explanation, there are differences in the perception of spatial properties in different modalities, but these differences do not stand in the way of the objectivity of perceptual experience.